2020
DOI: 10.32473/edis-in1270-2019
|View full text |Cite
|
Sign up to set email alerts
|

Brazilian Peppertree Thrips Pseudophilothrips ichini (Hood) (Insecta: Thysanoptera: Phlaeothripidae)

Abstract: The Brazilian peppertree thrips, Pseudophilothrips ichini (Hood) (Thysanoptera: Phlaeothripidae), is an insect native to Brazil (Figure 1). This species has been studied for the last 20+ years as a potential biological control agent of Brazilian peppertree, Schinus terebinthifolia Raddi (Sapindales: Anacardiaceae), in Florida (Cuda et al. 2008; Cuda et al. 2008; Manrique at al. 2014; Wheeler et al. 2016a, b). Host specificity experiments demonstrated that Pseudophilothrips ichini has a limited host range (Cuda… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The thrips naturally occur throughout the native range of Brazilian peppertree and has undergone extensive dietary host range studies in quarantine to ensure safety to beneficial native plant species. Studies have shown that Brazilian peppertree thrips selectively choose the Brazilian peppertree as their primary host and are effective at reducing growth rates, height, and number of green stems (Prade et al 2019). ERDC, BPUB, and other collaborators are evaluating the use of these thrips in the RBR restoration project as an adaptive management O&M strategy as well as analogous future projects in similarly infested resaca systems.…”
Section: Future Outlooksmentioning
confidence: 99%
“…The thrips naturally occur throughout the native range of Brazilian peppertree and has undergone extensive dietary host range studies in quarantine to ensure safety to beneficial native plant species. Studies have shown that Brazilian peppertree thrips selectively choose the Brazilian peppertree as their primary host and are effective at reducing growth rates, height, and number of green stems (Prade et al 2019). ERDC, BPUB, and other collaborators are evaluating the use of these thrips in the RBR restoration project as an adaptive management O&M strategy as well as analogous future projects in similarly infested resaca systems.…”
Section: Future Outlooksmentioning
confidence: 99%